Are Aortic Stent Grafts Safe in Pregnancy?. (1st July 2015) - Khandanpour, Nader; Mehta, Tapan A.; Adiseshiah, M.; Meyer, Felicity J.
Abstract : Aortic stent grafts are increasingly used to treat aortic aneurysms and also other aortic pathologies. The safety of aortic stent grafts in pregnancy has never been studied or reported. We report on two cases of aortic stent grafts in pregnant women and discuss the effect of pregnancy on these aortic stent grafts.